Subcellular organization of Streptomyces aureofaciens and overproduction of chlortetracycline - Hostálek, Z; Novotná, J; Starý, V; Kalachová, L; Vorísek, J (Biotechnology advances, 1990)
Biosynthesis of chlortetracycline is localized differently under low- and high-production conditions (standard low-production strain and its high-production variant). The experimental evidence was based on the assay of anhydrotetracycline oxygenase in subcellular fractions, ultracytochemical localization and electron-probe X-ray microanalysis of the product in the mycelium. Overproduction of chlortetracycline is closely associated with compartmentation of biosynthetic enzymes and with an efficient export of the antibiotic out of the cell.